City Production Strategies in the Neoliberalization Context - Salvador as Example - Pereira dos Santos, Maria Elisabete; Campos Borja, Patricia; Pedrassoli, Júlio; Santos, Alei Fernandes (Organizações & Sociedade, 2021)
The aim of the current article is to think over economic development and urban infrastructure propositions by Salvador 360 Strategic Plan from 2017, which was elaborated by the municipal government. The plan allows analyzing the neoliberal city production approach which, despite its modernizing profile, is just an update of old models that have great potential to worsen structural socio-spatial segregation issues. Neoliberalism, urban spoliation, land value and gentrification are key concepts in this article. Neil Brenner, Nick Theodore, Jamie Peck, David Harvey, Lúcio Kowarick, Carlos Vainer and Inaiá de Carvalho are its main theoretical references. The methodology addresses documental analysis, as well as the analysis of secondary data from official sources (DIEESE and IBGE) and digital platforms analysis (AirBnB website). Based on the results, Salvador 360 Strategic Plan deepens eviction processes experienced by the poor population in the city’s central zones and increases the appropriation of private urban added value and service provision concentration, within a political setback context. This process can aggravate urban environment precariousness and quality of life in the city.